Students’ Needs to Develop English Writing Materials - Dedi Sumarsono; Abdul Kadir Bagis; Moh. Arsyad Arrafii (Bina Nusantara University, 2017)
This research explored sophomore students’ needs in learning English writing at the Faculty of Education for Language and Arts, IKIP Mataram. To achieve this purpose, classroom observation, questionnaire, and documentation were conducted to collect data. Data were then analyzed descriptively, and triangulation of data analysis was also carried out. Based on the result of the questionnaire survey, the findings show that the students’ proficiency level is at the elementary level. Moreover, the students’ needs in learning writing include picture-enriched materials, academic writing, tourism-related topics, cooperative learning in use, and theories-driven writing materials. The findings are used as foundation knowledge to develop writing materials for students.